2007
DOI: 10.1007/s10452-007-9087-1
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of different phytoplankton functional groups in a Mediterranean reservoir

Abstract: A new high-resolution spectrofluorimetric probe and an automatic water-quality monitoring station (AWQMS) have been used to record seasonal variations in the spatial distribution of three functional groups of phytoplankton in a Mediterranean water-supply reservoir. In comparison with classical methods, the combined use of these innovative techniques enables development of faster and less laborious spatial distribution surveys, thus favouring higher-frequency and spatially more detailed measurements, and, conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 38 publications
0
32
1
Order By: Relevance
“…Our findings identified marked spatial variations during the development of the bloom, which was characterized by higher cell abundances in the middle and downstream parts of the reservoir. As in other studies (for example Hotto et al, 2007;Moreno-Ostos et al, 2008), this heterogeneous spatial distribution of Microcystis biomass might have been generated by greater cyanobacterial growth in areas where conditions for growth were better, or by displacement of the population by currents or winds, leading to an accumulation of a high cyanobacterial biomass in some areas. Some findings from the ITS genotyping suggested that both these processes were probably involved in the heterogeneous distribution of Microcystis biomass in the Grangent reservoir.…”
Section: Discussionmentioning
confidence: 61%
“…Our findings identified marked spatial variations during the development of the bloom, which was characterized by higher cell abundances in the middle and downstream parts of the reservoir. As in other studies (for example Hotto et al, 2007;Moreno-Ostos et al, 2008), this heterogeneous spatial distribution of Microcystis biomass might have been generated by greater cyanobacterial growth in areas where conditions for growth were better, or by displacement of the population by currents or winds, leading to an accumulation of a high cyanobacterial biomass in some areas. Some findings from the ITS genotyping suggested that both these processes were probably involved in the heterogeneous distribution of Microcystis biomass in the Grangent reservoir.…”
Section: Discussionmentioning
confidence: 61%
“…It has long been known that the spatial distribution of phytoplankton species is driven by interactions between physical and biological processes (Fietz et al, 2005;Hillmer et al, 2008) and that wind has an important role in these physical processes (George and Heaney, 1978;Schernewski et al, 2005;Moreno-Ostos et al, 2008;Alexander and Imberger, 2009;Pobel et al, in press). However, all existing knowledge was mainly based on the study of phytoplankton communities living in the well-mixed epilimnetic layer, the spatial distribution of which is affected by direct forcing by the wind.…”
Section: Discussionmentioning
confidence: 99%
“…Planktonic organisms are generally non-randomly distributed over a wide range of spatial scales and typically aggregate in complex three-dimensional structures which can be small-scale patches as well as systematic gradients (GEORGE and EDWARDS, 1976;GEORGE and HEANEY, 1978;REYNOLDS, 1993;GEORGE, 1993;MORENO-OSTOS et al, 2008a). Whilst phytoplankton spatial distribution patterns can be influenced by many physical, chemical and biological factors (GEORGE, 1993), the mesoscale distribution of phytoplankton is often 246 E. MORENO-OSTOS et al …”
Section: Introductionmentioning
confidence: 98%
“…Whilst phytoplankton spatial distribution patterns can be influenced by many physical, chemical and biological factors (GEORGE, 1993), the mesoscale distribution of phytoplankton is often a product of complex interactions between the hydrodynamics of the lake and the buoyant/sinking properties of phytoplankton (REYNOLDS, 2006;MORENO-OSTOS et al, 2008a;MORENO-OSTOS et al, 2009).…”
Section: Introductionmentioning
confidence: 99%